Chromosomal aberrations in lymphocytes of healthy subjects and risk of cancer - Rossner, Pavel; Boffetta, Paolo; Ceppi, Marcello; Bonassi, Stefano; Smerhovsky, Zdenek; Landa, Karel; Juzova, Dagmar; Srám, Radim J (Environmental health perspectives, 2005)
There is evidence that increased frequency of chromosomal aberration (CA) in peripheral blood lymphocytes is a predictor of cancer, but further data are needed to better characterize CA as marker of cancer risk. From the archives of 15 laboratories we gathered cytogenetic records of 11,834 subjects who were free of cancer at the moment of blood drawing and who underwent cytogenetic examination for preventive purposes in the Czech Republic during 1975-2000. We linked these records to the national cancer registry, revealing a total of 485 cancer cases. Subjects were classified according to the percentiles of CA distribution within each laboratory as low (0-33rd percentile), medium (34-66th percentile), and high (66-100th percentile). Subjects were further classified by occupational exposure and by subclass of CA. We found a significant association between the overall cancer incidence and the presence of chromosome-type aberrations [relative risk (RR) for high vs. low CA level = 1.24; 95% confidence interval (CI), 1.03-1.50] but not chromatid-type aberrations. Stomach cancer showed a strong association with frequency of total CA (RR = 7.79; 95% CI, 1.01-60.0). The predictivity of CA observed in subjects exposed to various classes of carcinogens did not significantly differ from the group of nonexposed subjects. This study contributes to validation of CA as a predictive marker of cancer risk, in particular, of stomach cancer; the association between CA frequency and cancer risk might be limited to chromosome-type aberrations.
Keywords: nádory žaludku; Registries; Stomach Neoplasms; Humans; Case-Control Studies; Lymphocytes; lymfocyty; registrace; studie případů a kontrol; Female; dospělí; lidé; Adult; chromozomální aberace; ženské pohlaví; Chromosome Aberrations; Male; Retrospective Studies; Neoplasms; nádory; retrospektivní studie; Risk Assessment; mužské pohlaví; hodnocení rizik